Benjamin Franklin, young printer - Stevenson, Augusta (Aladdin Books Collier Macmillan, 1986)
A biography of the young Philadelphia printer who grew up to become a world-renowned author, diplomat, scientist, and inventor, and one of the founding fathers of the United States.